Consumer Perception and Awareness towards Organic Food in the National Capital Region (Indian Journal of Extension Education, 2024)
The growing demand for organic food in recent years has led to increase an interest in studying consumers’ attitude and perception towards organic food products. The study explores consumer perception and awareness towards organic food in Haryana’s National Capital Region (NCR), with an emphasis on demographic variables and market dynamics. Primary data was collected from a sample of 300 respondents using a structured questionnaire between the months of September-October 2023 year. Factor analysis revealed two significant factors influencing consumers’ attitude were “Attitudes towards Organic Food” and “Consumer Perception and Market Dynamics.” While consumers in the NCR reflected positive attitudes towards organic food, driven by perceptions of health and environmental benefits, location was found to have no significant effect on attitudes but does influence perceptions of market dynamics. The study highlights the importance of consumer awareness and understanding market dynamics for promoting sustainable consumption patterns and engaging stakeholders in the organic food industry. Overall, these findings contribute to a better understanding of consumer behavior towards organic food products in the context of the NCR region, offering insights for policymakers, farmers, and industry stakeholders to promote organic food consumption and production.